Analisis Penerimaan Financial Technologi terhadap UMKM melalui Inklusi Keuangan di Kota Semarang: Penelitian - Luthfia Nurul Ichsani; Luluk Muhimatul Ifada (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
MSMEs play a strategic role in the Semarang City economy, and the development of financial technology presents an opportunity to expand financial access and maintain business sustainability. This study aims to examine the effect of fintech adoption on MSME sustainability, with financial inclusion as a mediating variable. The method used was a quantitative approach through a survey of 134 MSME fintech users using purposive sampling. The analysis results indicate that fintech adoption has a positive and significant effect on financial inclusion and MSME sustainability. Financial inclusion has also been shown to positively influence MSME sustainability and mediate the relationship between fintech adoption and business sustainability. These findings confirm that fintech adoption supported by increased financial inclusion can strengthen the sustainability of MSMEs in Semarang City.